Evidence and potential mechanisms of traditional Chinese medicine for the treatment of psoriasis vulgaris: a systematic review and meta-analysis. (17th February 2022) - Dai, Dan; Wu, Haoran; He, Chunyan; Wang, Xinmiao; Luo, Yiqi; Song, Ping
Abstract: Psoriasis vulgaris (PV) not only affects patients' skin health but also increases the risk of coronary heart disease and diabetes, which brings both physical and mental harms. Its pathogenesis is complex, and the multitarget effect of traditional Chinese medicine (TCM) is especially advantageous. Because a considerable number of randomized controlled trials related to TCM exhibit design defects, small sample size, or inadequate intervention time, so the status of TCM in the treatment of PV cannot be fully clarified. We reviewed the controlled clinical trials published over the past decade and selected 17 high-quality articles from over 2000 papers. The results suggest that TCM might be beneficial for decrease in PASI scores, thus, TCM might be an effective alternative therapy for PV management. The safety of TCM on PV was also assessed in our analysis. The more strictly designed and long-term observations of TCM for PV are supposed to be conducted in the future.